An Evidenced-Based Scale of Disease Severity following Human Challenge with Enteroxigenic Escherichia coli - Porter, Chad K.; Riddle, Mark S.; Alcala, Ashley N.; Sack, David A.; Harro, Clayton; Chakraborty, Subhra; Gutierrez, Ramiro L.; Savarino, Stephen J.; Darsley, Michael; McKenzie, Robin; DeNearing, Barbara; Steinsland, Hans; et al. (PloS one, 2016)
Experimental human challenge models have played a major role in enhancing our understanding of infectious diseases. Primary outcomes have typically utilized overly simplistic outcomes that fail to entirely account for complex illness syndromes. We sought to characterize clinical outcomes associated with experimental infection with enterotoxigenic Escherichia coli (ETEC) and to develop a disease score. Data were obtained from prior controlled human ETEC infection studies. Correlation and univariate regression across sign and symptom severity was performed. A multiple correspondence analysis was conducted. A 3-parameter disease score with construct validity was developed in an iterative fashion, compared to standard outcome definitions and applied to prior vaccine challenge trials. Data on 264 subjects receiving seven ETEC strains at doses from 1x105 to 1x1010 cfu were used to construct a standardized dataset. The strongest observed correlation was between vomiting and nausea (r = 0.65); however, stool output was poorly correlated with subjective activity-impacting outcomes. Multiple correspondence analyses showed covariability in multiple signs and symptoms, with severity being the strongest factor corresponding across outcomes. The developed disease score performed well compared to standard outcome definitions and differentiated disease in vaccinated and unvaccinated subjects. Frequency and volumetric definitions of diarrhea severity poorly characterize ETEC disease. These data support a disease severity score accounting for stool output and other clinical signs and symptoms. Such a score could serve as the basis for better field trial outcomes and gives an additional outcome measure to help select future vaccines that warrant expanded testing in pivotal pre-licensure trials.